Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Quân Lưu Minh
Akai Haruma
11 tháng 12 2022 lúc 15:16

Lời giải:

$a^2+b^2+c^2=ab+bc+ac$

$\Leftrightarrow 2a^2+2b^2+2c^2-2ab-2bc-2ac=0$

$\Leftrightarrow (a^2-2ab+b^2)+(b^2-2bc+c^2)+(c^2-2ac+a^2)=0$

$\Leftrightarrow (a-b)^2+(b-c)^2+(c-a)^2=0$

Mà $(a-b)^2; (b-c)^2; (c-a)^2\geq 0$ với mọi $a,b,c$ nên để tổng của chúng bằng $0$ thì:

$(a-b)^2=(b-c)^2=(c-a)^2=0$

$\Rightarrow a=b=c$

Khi đó:

$a^3+b^3+c^3=3a^3$

$3abc=3a^3$

$\Rightarrow a^3+b^3+c^3=3abc$ (đpcm)


Các câu hỏi tương tự
hello
Xem chi tiết
Nguyễn Thanh Huyền
Xem chi tiết
Trang Lương
Xem chi tiết
Tho Vo
Xem chi tiết
huy dương
Xem chi tiết
Trần Ngọc Liên
Xem chi tiết
duong hong anh
Xem chi tiết
Thùy Linh
Xem chi tiết
nguyễn Ngọc Thùy Dương
Xem chi tiết
Uzumaki Naruto
Xem chi tiết